RECOGNITION AND ENFORCEMENT OF INTERNATIONAL ARBITRATION AWARDS: A CASE STUDY OF UZBEKISTAN (Eureka Journal of Humanities and Social Research, 2026)
This article examines the legal framework and judicial practice of recognition and enforcement of international arbitral awards in Uzbekistan. Emphasis is placed on the distinction between recognition and enforcement as two interconnected but conceptually different stages of giving legal effect to arbitral awards. The study analyzes Uzbekistan’s obligations under the 1958 New York Convention and the extent to which national legislation, particularly the Economic Procedural Code and the Law “On International Commercial Arbitration,” complies with international standards. Based on an analysis of court practice from 2019–2024, the article identifies key challenges faced by Uzbek courts, including issues of proper notification of parties, procedural guarantees, language of proceedings, and the limits of judicial review of arbitral awards. The findings demonstrate a generally pro-enforcement approach in judicial practice, while also revealing areas requiring more consistent interpretation and closer judicial scrutiny to enhance legal certainty and investor confidence.
Keywords: International arbitration; recognition and enforcement; New York Convention; Model law; arbitral awards; judicial practice in Uzbekistan